Factors affecting aseptic loosening in primary total knee replacements: an in vitro study - David Lionberger; Laura Wattenbarger; Christopher Conlon; Timothy J. Walker (Journal of Experimental Orthopaedics, 2020)
Abstract Background Implant surface integrity and cement bonding are assumed to be sufficient in primary total knee replacements to stabilize implants for extended wear without concerns over delamination and loosening. Yet there exists a significant rate of aseptic loosening where failure at implant cement interface occurs. The aim of this study is to look at specific aspects leading to aseptic loosening of the total knee replacement, where cement adhesion to the implant results in the lowest pull off strength. Methods Virgin ceramic coated and uncoated chrome cobalt tibial trays were used in a pull off study using differing viscosities of cement at varied time intervals to compare which combination is strongest compared to which is least resistant to pull off testing. Results Low viscosity cement had a 44% (5.9 kg verses 3.3 kg, p < 0.001) higher pull-off strength compared to high viscosity cement. Coated implants had a 30% (3.9 kg verses 5.5 kg, p = 0.037) lower pull-off strength compared to non-coated. Testing measures were limited to cement utilization less than 5 minutes due to the poor adhesion of the dowels beyond this time. Finally, there was a significant difference in adhesion properties between brand names when utilizing low viscosity cement on the non-coated trays (10.34 kg for Simplex verses 4.87 for Palacos, p = 0.021). Conclusion There are differences in adhesion properties between cement vendors, prompting significant concerns over the use of coated implants with particular cement types. Use of low viscosity cement on non-coated surfaces in the early liquid phase of cement curing was found to produce the best chance for adequate adhesion. This study demonstrates that there is variation in the adhesive properties of implants utilized in total knee replacements, and that the orthopedic community should consider not only the implant, cement, and curing time individually, but the overall integrity conferred from the combination of all of these variables.